Education on Prevention of Hypercholesterolemia and Hypertension by Consuming Sardeljondan Herbal Drinks: Edukasi Pencegahan Hiperkolesterolemia dan Hipertensi dengan Mengonsumsi Minuman Herbal Sardeljondan - Lukiyono, Yauwan Tobing; Firdaus, Abraham Ahmad Ali; Zain, Salfa Salsabilah; Rahmawati, Anis Hanifa; Zulviah, Nur (Jurnal Soeropati, 2022)
Hypertension is a condition in which a person experiences an increase in systolic blood pressure of more or equal to 140 mmHg and diastolic blood pressure of more or equal to 90 mmHg. Currently, the estimated number of cases of hypertension in Indonesia is 63,309,620 people, while the death rate due to hypertension in Indonesia is 427,218 deaths. Currently, the prevalence of hypercholesterolemia is still very high. The prevalence of hypercholesterolemia in the world is around 45%. The high incidence of hypertension and hypercholesterolemia can also be caused by low public knowledge about blood pressure and cholesterol levels, starting from ways to prevent them, the course of the disease, its symptoms, to the treatment of the disease. In addition, lifestyle and diet also affect the high incidence of hypertension and hypercholesterolemia. Both of these diseases can cause more serious complications, such as heart disease and stroke. Therefore, an effort is needed to increase public knowledge about hypertension and hypercholesterolemia, as well as introduce alternative herbal drinks that are efficacious for people with hypertension and hypercholesterolemia.